EAN consensus review on prevention, diagnosis and management of tick‐borne encephalitis. (1st August 2017) - Taba, P.; Schmutzhard, E.; Forsberg, P.; Lutsar, I.; Ljøstad, U.; Mygland, Å.; Levchenko, I.; Strle, F.; Steiner, I.
Abstract : Background and purpose: Tick‐borne encephalitis (TBE) is an infection of the central nervous system (CNS) caused by tick‐borne encephalitis virus (TBEV) and transmitted by ticks, with a variety of clinical manifestations. The incidence of TBE in Europe is increasing due to an extended season of the infection and the enlargement of endemic areas. Our objectives are to provide recommendations on the prevention, diagnosis and management of TBE, based on evidence or consensus decisions. Methods: For systematic evaluation, the literature was searched from 1970 to 2015 (including early online publications of 2016), and recommendations were based on evidence or consensus decisions of the Task Force when evidence‐based data were not available. Recommendations: Vaccination against TBE is recommended for all age groups above 1 year in highly endemic areas (≥5 cases/100 000/year), but also for individuals at risk in areas with a lower incidence. Travellers to endemic areas should be vaccinated if their visits will include extensive outdoor activities. Post‐exposure prophylaxis after a tick bite is not recommended. A case of TBE is defined by the presence of clinical signs of meningitis, meningoencephalitis or meningoencephalomyelitis with cerebrospinal fluid (CSF) pleocytosis (>5 × 10 6 cells/l) and the presence of specific TBEV serum immunoglobulin M (IgM) and IgG antibodies, CSF IgM antibodies or TBEV IgG seroconversion. TBEV‐specific polymerase chain reaction in blood is diagnostic in the first viremic phase but it is not sensitive in the second phase of TBE with clinical manifestations of CNS inflammation. Lumbar puncture should be performed in all patients with suspected CNS infection unless there are contraindications. Imaging of the brain and spinal cord has a low sensitivity and a low specificity, but it is useful for differential diagnosis. No effective antiviral or immunomodulating therapy is available for TBE; therefore the treatment is symptomatic. Patients with a potentially life threatening meningoencephalitis or meningoencephalomyelitis should be admitted to an intensive care unit. In the case of brain oedema, analgosedation should be deepened; osmotherapy and corticosteroids are not routinely recommended. If intracranial pressure is increased, therapeutic hypothermia or decompressive craniectomy might be considered. Seizures should be treated as any other symptomatic epileptic seizures. Conclusions: Tick‐borne encephalitis is a viral CNS infection that may result in long‐term neurological sequelae. Since its incidence in Europe is increasing due to broadening of endemic areas and prolongation of the tick activity season, the health burden of TBE is enlarging. There is no effective antiviral treatment for TBE, but the disease may be effectively prevented by vaccination.